Jack London, photographer - Reesman, Jeanne Campbell (University of Georgia Press, 2010)
"Jack London (1876-1916) remains one of the most widely read American writers, known for his naturalist fiction, socialist novels and essays, journalism, and the many adventures that he shared with the world. London was also an accomplished photographer, producing nearly twelve thousand photographs during his lifetime. Jack London, Photographer, the first book devoted to London's photography, reveals a vital dimension of his artistry, barely known until now. The volume's more than two hundred photographs were printed from the original negatives in the California State Parks collection and from the original photographs in albums at the Huntington Library. They are reproduced here as duotones from silver gelatin prints. The general and chapter introductions place London's photographs in the context of his writings and his times"--P. [2] of dust jacket.